The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1371/journal.pone.0164638
|View full text |Cite
|
Sign up to set email alerts
|

Poor Compliance to Hormone Therapy and Decreased Bone Mineral Density in Women with Premature Ovarian Insufficiency

Abstract: Premature ovarian insufficiency leads to through infertility and estrogen deficiency. Optimal management encompasses estrogen replacement therapy. Long-term outcome of women with POI is not known. We design a study to evaluate the medical care, hormone replacement therapy compliance and bone mineral density (BMD) in POI women with at least a five-year follow-up after the first evaluation. One hundred and sixty-two patients (37.3±8.0 years) were evaluated (follow-up 7.9±2.8 years). Sixty-nine patients (42.6%) h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 26 publications
0
14
0
1
Order By: Relevance
“…Osteoporosis is a key concern for women with POI 43,44 , with estimated prevalence rates ranging from 8% to 27% according to the definition used (BMD or fracture) and the cause of POI 12,[103][104][105] . Women with POI have significantly lower BMD 105,106 and an increased risk of osteoporosis compared to women with usual age at menopause (odds ratio 2.54; 95% CI 1.63-3.96) 12 , especially in women younger than 70 years 12,105 .…”
Section: Bone Health In Women With Premature Ovarian Insufficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…Osteoporosis is a key concern for women with POI 43,44 , with estimated prevalence rates ranging from 8% to 27% according to the definition used (BMD or fracture) and the cause of POI 12,[103][104][105] . Women with POI have significantly lower BMD 105,106 and an increased risk of osteoporosis compared to women with usual age at menopause (odds ratio 2.54; 95% CI 1.63-3.96) 12 , especially in women younger than 70 years 12,105 .…”
Section: Bone Health In Women With Premature Ovarian Insufficiencymentioning
confidence: 99%
“…Identified risk factors for low BMD incorporate both generally recognized and cause-specific factors and, in women with spontaneous normal karyotype POI, include age <20 years at onset of irregular menses, >1 year delay in diagnosis, low serum vitamin D concentrations, low dietary calcium, non-compliance with HT, and lack of exercise 103,106 . Women with Turner syndrome may have additional contributors to bone loss including genetically related skeletal fragility, increased risk of celiac disease, and increased risk of falls secondary to hearing loss and visuospatial abnormalities 107 .…”
Section: Bone Health In Women With Premature Ovarian Insufficiencymentioning
confidence: 99%
“…В ходе проведённого исследования было выявлено, что возраст достоверно является одним из очень важных признаков, влияющих отрицательно на плотность костной ткани, что подтверждается и многими другими исследованиями, в том числе и по данным компьютерной томографии [11]. Вторым не менее важным фактором, снижающим плотность костной ткани, является дефицит половых гормонов [12]. В связи с комбинацией этих причин снижение плотности костной ткани отчетливо и достоверно проявилось по данным наших исследований стенок верхнечелюстного синуса в период менопаузы (р < 0,05) в первой исследуемой группе женщин 50 и старше лет с ИМТ 18,5-24,9 кг/м 2 по сравнению с контрольной группой.…”
Section: материалы и методыunclassified
“…Sex steroid replacement therapy restores bone density in young patients with ovarian function depletion [ 3 ]. The results of the study by Bachelot et al revealed significant reduction in femur BMD and an increased incidence of osteopaenia and osteoporosis in the group of women with POI, who discontinued HRT after one year of treatment, compared to women who continued it for at least five years [ 8 ]. Treatment with transdermal oestradiol and vaginal progesterone has a more beneficial effect on the bone mass in the lumbar spine than standard HTM [ 9 ].…”
Section: Bone Health Consequencesmentioning
confidence: 99%
“…However, the compliance among the POI patients is low. Around 40% of POI patients discontinue the therapy within the first year of treatment [ 8 , 9 ]. The patient’s preferences for optimal route, drug, and type of hormonal therapy should be key in the choice of treatment.…”
Section: Choice Of Oestrogen/progestogen Formulationmentioning
confidence: 99%